PERAN ORANG TUA SEBAGAI SUMBER PENDIDIKAN KARAKTER BAGI ANAK USIA DINI - Andhika, Muhammad Rezki (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID) Ciamis Jawa Barat, 2021)
This paper examines the role of parents as a source of character education for early childhood. This study was conducted using the library research method. The results of this study indicate that the role of parents is a determining factor for children's development, both physically and mentally, is the role of both parents as the first and main educators for children who are born until they are adults. In the process of forming knowledge, through various parenting styles conveyed by parents is very important. Education in the family plays a very important role in developing the character, personality, cultural values, religious and moral values ​​and simple skills of children. The role of parents in influencing the character of children is no longer borne by the mother only. The role of the father in shaping the character of the child is very large. The assumption is that the father's job is to earn money and the mother to raise children and take care of the household, but the father's role in raising or caring for and educating the children is still needed. This assumption does seem ideal, but in practice it cannot be applied rigidly. It is better if fathers are still obliged to participate in maintaining interactions with their children, such as inviting them to talk, joke, and play.